Preliminary Study on the Measurement of Cadmium Levels in Scavenger Hair at Sukawinatan Landfill Palembang (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Cadmium (Cd) is a toxic heavy metal with the potential to contaminate the environment, particularly in landfill sites using open dumping systems, such as the Sukawinatan Landfill in Palembang. This study aims to measure Cd levels in scavengers’ hair as an indicator of heavy metal exposure. A cross-sectional study design was conducted in January 2024, with hair samples collected from five respondents using purposive sampling techniques. Cd levels were measured using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that Cd levels in the scavengers' hair ranged from 0.31 to 0.99 ppm, exceeding the normal limit set which is